Analisis Investasi Usahatani Pembibitan Sapi Peranakan Limousine di Kabupaten Sleman - Shanti Emawati; Rini Widiati; I Gede Suparta Budisatria (Universitas Sebelas Maret (UNS), 2008)
The research was conducted to determine the feasibility of financial investment on Limousine cattle farming. Research was done from January to May 2007, located in Sleman District. Survey methods was done to collect primary data at the farm level and secondary data from related institution. Purposive sampling was applied to sellect farmers’ respondent. Criteria used to analyze the feasibility of financial investment were consisted of Benefit Cost Ratio (BCR), Net Present Value (NPV), Internal Rate of Return (IRR) and Payback Period (PPC), based on 7 years investment and 12% annual discount factor. The result showed that based on NPV, IRR, BCR and payback period analysis, the most feasible investment of Limousine cattle breeding farm under farmers’ condition with the value of NPV = Rp 11.900.156,00, IRR = 32,64%, BCR = 1,74 and payback period = 3,25 years. Keywords : Limousine cattle, Cattle breeding farm, Investment financial analysis